Corporate Sustainability:: A Case Study at Mãe de Deus Hospital - Froehlich, Cristiane; Bitencourt, Claudia Cristina (Sustainability in Debate, 2015)
This paper aims to analyze the pillars of sustainability contemplated in the management model of the Mãe de Deus Hospital, located in Porto Alegre, Rio Grande do Sul, Brazil. This qualitative and descriptive research is based on a case study seeking to highlight the pillars of sustainability management based on organizational practices. Data were collected through semi-structured interviews conducted with nine hospital executives and were analyzed using qualitative content analysis with N-Vivo software support. Main results show that since 2000 the concept of corporate sustainability has been embedded in business management models that consider economic and social pillars as a part of the decision-making process. These relevance of these pillars rely upon several factors, such as: a) economic factors ”“ the need for the self-sustainability of the hospital network; b) social factors - the nature of business and the mission of the religious congregation, which is based on humanization values.